2013
DOI: 10.1021/ol402887z
|View full text |Cite
|
Sign up to set email alerts
|

Oxonium Ylide Rearrangement of Enzymatically Desymmetrized Glutarates

Abstract: The combination of an enzyme-mediated enantioselective desymmetrization of readily available 3-benzyloxyglutarates and subsequent rhodium-catalyzed oxonium ylide rearrangement of their corresponding in situ derived diazo ketones offers a very concise and highly stereoselective access to functionalized tetrahydrofuranone building blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Under similar conditions (butynyl trichloroacetimidate, TMSOTf, DCM, RT), propargylation yielded 2 k in 60 % . As already disclosed in our previous communication, benzylic ethers were accessible via a Lewis acid‐mediated, reductive etherification to give rise to 2 e–2 j in moderate to good yields (46–82 %). Finally, two alkoxymethyl ethers were synthesized by treatment of alcohol 1 with the respective alkoxymethyl chlorides and Hünig's base ( 2 l , 60 %; 2 m , 64 %).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Under similar conditions (butynyl trichloroacetimidate, TMSOTf, DCM, RT), propargylation yielded 2 k in 60 % . As already disclosed in our previous communication, benzylic ethers were accessible via a Lewis acid‐mediated, reductive etherification to give rise to 2 e–2 j in moderate to good yields (46–82 %). Finally, two alkoxymethyl ethers were synthesized by treatment of alcohol 1 with the respective alkoxymethyl chlorides and Hünig's base ( 2 l , 60 %; 2 m , 64 %).…”
Section: Resultssupporting
confidence: 62%
“…The major isomer 6 was crystallized and X‐ray crystal structure analysis unambiguously confirmed the anticipated connectivity and relative stereochemistry resulting from the previous oxonium ylide rearrangement step (see Supporting Information for ORTEP and crystallographic data). The thus obtained alcohols can on one side be used as functional building blocks towards more complex heterocyclic targets, but could also act as precursors for 2,5‐disubstituted tetrahydrofurans through Barton–McCombie deoxygenation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the yields and diastereoselectivities of desired tetrahydrofuranone products were relatively low (Scheme 5 ). 22 Moreover, after systematic evaluation of catalysts, the authors found the transformation to be catalyst-dependent. In different catalytic systems, the [1,2]- and [2,3]-rearrangements could be achieved selectively with [Cu(MeCN) 4 ]PF 6 or Rh 2 (oct) 4 as catalyst.…”
Section: Substrate-induced Asymmetric [12]-stevens-type Rearrangementmentioning
confidence: 99%
“…Prochiral 3-benzyloxyglutarates have been subjected to a Candida antarctica lipase B (CALB) mediated desymmetrisation (Scheme 9). 30 Conversion of the resulting carboxylic acid into a diazo ketone and rhodium catalysed oxonium ylide rearrangement allowed access to functionalised tetrahydrofuranone building blocks.…”
mentioning
confidence: 99%